Pembekalan Mahasiswa di STAK PESAT Salatiga Bertajuk “Mengenali dan Mengelola Emosi” - Debora Tiurlan Tambunan (Journal Of Social Empowerment Publications, 2024)
Adolescence, the period currently being experienced by college students, is the most important and dynamic period in the development of human emotions. Individuals who have emotional intelligence are individuals who can adapt in various situations and are able to establish good relationships with other humans. Realizing the importance of this, an education program entitled "Recognizing and Managing Emotions" at STAK PESAT Salatiga was held on Monday, August 5th 2024. Using a collaboration of lecture, discussion and practice methods, the training was held for two sessions with two focus topics in each session, namely recognizing emotions and managing emotions. The positive responses given by each participant at the end of the program stated that this provision made them aware to the emotions they felt and helped them respond to every emotion they experienced.